(untitled) (Lehahayer, 2026)
THE LEGACY OF MAJOR MELIK SOMCHJANC AND HIS FAMILY IN THE COLLECTIONS OF THE CENTER FOR DOCUMENTATION OF DEPORTATIONS, EXPULSIONS AND RESETTLEMENTS OF THE UNIVERSITY OF THE NATIONAL EDUCATION COMMISSION IN KRAKÓW The article discusses materials in the collection of the Center for Documentation of Deportations, Expulsions and Resettlements of the University of the National Education Commission in Kraków relating to major Melik Somchjanc (1900-1979), an Armenian born in Georgia under Russian rule, an officer of the Polish Army, participant in the anti-Soviet Promethean movement during the interwar period, and a hero of the Western Front in the Second World War, as well as his closest relatives: his wife Władysława, his son Zbigniew, and his daughter-in-law Zofia. These documents and artefacts constitute an intriguing set illustrating the fate of an Armenian-Polish family from the south-eastern borderlands of Poland, whose members experienced the cataclysm of the war in various places and circumstances (the Soviet Union, Africa), and subsequently found itself in political exile in postwar Great Britain, where they spent the reminder of their lives.